Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Help With a Calculus Problem?

{ 1/(x^2+4) dx

Use the substitution x=2tanx

your final answer should be in terms of x.

Please show work

5 Answers

Relevance
  • 9 years ago
    Favorite Answer

    If we're going to replace x with 2 tan y (we should use a different variable, otherwise we're saying x = 2 tan x, which limits x to certain values), then we need to evaluate dx as well.

    To do that, we use dx/dy = d/dy (2 tan y), and then multiply both sides by dy.

    In order to take the derivative of 2 tan y with respect to y, I'll make use of the trig relation tan y = sin y / cos y.

    d/dy (2 tan y) = 2 d/dy (sin y / cos y)

    Now, because I can only remember the product rule and never the quotient rule,

    d/dy (2 tan y) = 2 d/dy [sin y * (cos y)^-1]

    d/dy (2 tan y) = 2 {d/dy (sin y) * (cos y)^-1 + sin y d/dy [(cos y)^-1]}

    Now, from the chain rule and power rule,

    d/dy (2 tan y) = 2 {d/dy (sin y) * (cos y)^-1 + sin y * [-1 * (cos y)^-2 * d/dy (cos y)]}

    You should know that the deriviative of sine is cosine, and the derivative of cosine is -sine.

    d/dy (2 tan y) = 2 {cos y * (cos y)^-1 + sin y * [-1 * (cos y)^-2 * -sin y]}

    d/dy (2 tan y) = 2 {cos y / cos y + sin y * [(cos y)^-2 * sin y]}

    d/dy (2 tan y) = 2 {1 + (sin y)^2 / (cos y)^2}

    d/dy (2 tan y) = 2 [(cos y)^2 + (sin y)^2] / (cos y)^2

    Now, from the Pythagorean theorem, we know sin^2 y + cos^2 y = 1, so

    d/dy (2 tan y) = 2 * 1 / (cos y)^2

    d/dy (2 tan y) = 2 / (cos y)^2

    Now, we go back to

    dx/dy = d/dy (2 tan y)

    dx/dy = 2 / (cos y)^2

    dx = 2 / (cos y)^2 * dy

    Now, back to the original integral. Replacing x with 2 tan x, and dx with 2 / (cos y)^2 * dy,

    ∫1 / (x^2 + 4) dx = ∫1 / [(2 tan y)^2 + 4] * 2 / (cos y)^2 * dy

    ∫1 / (x^2 + 4) dx = 2 ∫1 / {[(2 tan y)^2 + 4] * (cos y)^2} * dy

    ∫1 / (x^2 + 4) dx = 2 ∫1 / {[4 (tan y)^2 + 4] * (cos y)^2} * dy

    ∫1 / (x^2 + 4) dx = 2 / 4 * ∫1 / {[(tan y)^2 + 1] * (cos y)^2} * dy

    ∫1 / (x^2 + 4) dx = 1/2 * ∫1 / {[(tan y)^2 + 1] * (cos y)^2} * dy

    Now, replacing tan y with sin y / cos y,

    ∫1 / (x^2 + 4) dx = 1/2 * ∫1 / {[(sin y / cos y)^2 + 1] * (cos y)^2} * dy

    ∫1 / (x^2 + 4) dx = 1/2 * ∫1 / {[(sin y)^2 / (cos y)^2 + 1] * (cos y)^2} * dy

    ∫1 / (x^2 + 4) dx = 1/2 * ∫1 / [(sin y)^2 + (cos y)^2] * dy

    Using the Pythagorean theorem,

    ∫1 / (x^2 + 4) dx = 1/2 * ∫1 / 1 * dy

    ∫1 / (x^2 + 4) dx = 1/2 * ∫dy

    ∫1 / (x^2 + 4) dx = 1/2 * y + C

    Don't forget, since this is an indefinite integral, we need to add an unknown constant term. Now, replace y with x. Recall that x = 2 tan y, so y = arctan (x / 2)

    ∫1 / (x^2 + 4) dx = 1/2 * arctan (x / 2) + C

    I hope that helps!

  • 5 years ago

    f (x) = x^3 - 12x + a million . . . the 1st spinoff set to 0 famous turning or table sure factors f ' (x) = 3x^2 - 12 3x^2 - 12 = 0 3 * (x + 2) * (x - 2) = 0 x = 2 ... x = - 2 . . . the 2nd spinoff evaluated at x = 2 and -2 determines if those factors are min, max, or neither. f ' ' (x) = 6x f ' ' (2) = 6*2 = 12 <== beneficial fee shows x=2 is a interior sight minimum f ' ' (-2) = 6*(-2) = -12 <== damaging fee shows x=-2 is a interior sight optimal a.) x = - 2 is a optimal, and x=2 is a minimum ... so x = - infinity to -2 is increasing x = -2 to +2 is reducing x = +2 to + infinity is increasing b.) f (-2) = (-2)^3 - 12*(-2) + a million = 17 f (2) = (2)^3 - 12*(2) + a million = - 15 c.) . . . the 2nd spinoff set to 0 famous inflection factors, or the place concavity ameliorations 6x = 0 x = 0 <=== inflection element x = - 2 is a optimal, so could desire to be concave down concavity ameliorations on the inflection element(s) ... so x = - infinity to 0 is concave down x = 0 to + infinity is concave up

  • x = 2 * tan(t) would be a better substitution

    x = 2 * tan(t)

    dx = 2 * sec(t)^2 * dt

    dx / (x^2 + 4) =>

    (2 * sec(t)^2 * dt) / ((2 * tan(t))^2 + 4) =>

    (2 * sec(t)^2 * dt) / (4 * tan(t)^2 + 4) =>

    (2 * sec(t)^2 * dt) / (4 * (1 + tan(t)^2)) =>

    (2 * sec(t)^2 * dt / (4 * sec(t)^2) =>

    (1/2) * dt

    Integrate

    (1/2) * t + C

    x = 2 * tan(t)

    x/2 = tan(t)

    t = arctan(x/2)

    (1/2) * arctan(x/2) + C

  • ?
    Lv 4
    9 years ago

    ∫ 1/(x² + 4) dx

    x = 2 tan t

    t = arctan (x/2)

    dx = 2 sec² t dt

    ∫ 1/(x² + 4) dx

    = ∫ 1/((2 tan t)² + 4) (2 sec² t dt)

    = ∫ 1/(4 tan² t + 4) (2 sec² t dt)

    = ∫ 1/(4(tan² t + 1)) (2 sec² t dt)

    = ∫ 1/(4 sec² t) (2 sec² t dt)

    = ∫ (1/2) dt

    = (1/2)t + C

    = (1/2)(arctan (x/2)) + C

  • How do you think about the answers? You can sign in to vote the answer.
  • 9 years ago

    Substitute x = 2*tan(t):

    ∫2*sec²(t) dt/4*sec²(t) =t/2 + C = arctan(x/2) + C

Still have questions? Get your answers by asking now.